ISOLASI DAN BIOINHIBITOR AKTIVITAS ENZIM TIROSINASE DARI EKSTRAK ETIL ASETAT PADI HITAM (Oryza Sativa L Indica) - Agus Rochmat; LBS Kardono; Dewi Puspa Lotulung (BORNEO JOURNAL OF PHARMASCIENTECH, 2019)
ABSTRACT Melanin is a color pigment in the skin, hair, eye choroid layers, and certain tumor cells. The process of melanin formation in the human body can reduced by several mechanisms, such as antioxidants, tyrosine enzyme inhibitors, and hormonal activity. The process of formation of melanin or pigment in human skin occurs with the help of biocatalysts (enzymes) and ultraviolet (UV) rays found in the sun. Biocatalysts that play a role in this browning reaction are tyrosine which can found in animals, plants and humans. The process of extracting black rice using methanol then continued by separation using column chromatography. The yield of ethyl acetate fraction was 3.26%. The highest yield was 4.1 mg with the characteristics: maximum wavelength of UV light at 298 nm, the name of the isovanillic acid compound and IC50 tyrosine inhibition test of 107.91 ppm Keywords: black rice, tyrosine enzym, isovanillic acid